The Effectiveness of Using the Digital-Based Flipped Classroom Model in Learning German Grammar level A2.1 - Lestuny, Carolina (Pattimura University, 2022)
The importance of using technology must be a form of today’s learning. To realize student-centered learning, a supportive learning model is needed. Learning German grammar is one of the subjects which considered quite difficult because it requires a good and right understanding in specified time. This research was aimed to know the effectiveness of digital-based flipped classroom model in learning German grammar level A2.1. The method was quasi-experimental design. The experimental design used one group pre test-post test. The instruments used in this study were tests, questionnaires and observation sheets. The results of the data analysis showed the mean value of the pre-test was 48.82 and the mean value of the post-test was 77.35. Thus there is an increase after using the flipped classroom, which is 28.53. From the calculation, the average value of N-Gain score was 57.14%, so it can be concluded that the use of flipped classroom is quite effective in learning German grammar level A2.1. This statment is reinforced by the results of the questionnaire which concludes that most students think that flipped classrooms need to be applied in learning German grammar level A2.1.